Secretul doctorului Walter (eseu psihanalitic) - Simona Galațchi (Revista de Istorie și Teorie Literară)
The article offers a synthetic sheet of the character Dr. Walter in Hortensia PapadatBengescu’s novels (Fecioarele despletite [The Dishevelled Maidens], Drumul ascuns [The Hidden Way] and Străina [The Stranger Woman]). The analysis of the data recorded in this sheet resorts to the psychoanalytic grid, envisaging at the same time some concepts of analytical psychology. It can be noticed, from this perspective, that Dr. Walter displays a prevailing death instinct (Thanatos instinct) which explains the path of his existence. He is a (self-)sacrificed savior, a lover of death. A man who always walks with death in his soul, with his attention almost totally absorbed by death, a man who offers himself, indifferently and without protest, contemplating death. Here lies “the secret” of Doctor Walter.